2014
DOI: 10.1128/iai.01339-13
|View full text |Cite
|
Sign up to set email alerts
|

GRA25 Is a Novel Virulence Factor of Toxoplasma gondii and Influences the Host Immune Response

Abstract: The obligate intracellular parasite Toxoplasma gondii is able to infect a broad range of hosts and cell types due, in part, to the diverse arsenal of effectors it secretes into the host cell. Here, using genetic crosses between type II and type III Toxoplasma strains and quantitative trait locus (QTL) mapping of the changes they induce in macrophage gene expression, we identify a novel dense granule protein, GRA25. Encoded on chromosome IX, GRA25 is a phosphoprotein that is secreted outside the parasites and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 45 publications
2
51
0
Order By: Relevance
“…Consistent with the NF-κB results, GRA15 and GRA25 , which encode two dense granule proteins known to modulate NF-κB activity and chemokine secretion (Ccl2 and Cxcl1), respectively, during infection with tachyzoites [62,78], were expressed in both forms albeit at somewhat higher levels in the infecting sporozoites. Transcripts encoding other well-characterized tachyzoite effectors [51,53], namely ROP16, ROP5, and ROP18 were also all expressed at similar levels in both sporozoites and tachyzoites.…”
Section: Discussionsupporting
confidence: 74%
“…Consistent with the NF-κB results, GRA15 and GRA25 , which encode two dense granule proteins known to modulate NF-κB activity and chemokine secretion (Ccl2 and Cxcl1), respectively, during infection with tachyzoites [62,78], were expressed in both forms albeit at somewhat higher levels in the infecting sporozoites. Transcripts encoding other well-characterized tachyzoite effectors [51,53], namely ROP16, ROP5, and ROP18 were also all expressed at similar levels in both sporozoites and tachyzoites.…”
Section: Discussionsupporting
confidence: 74%
“…Given that CCL22 induction in PHT cells required live parasites and was not induced by N. caninum , we reasoned that CCL22 induction was likely the result of a T. gondii -specific parasite effector that would be secreted after host cell invasion. T. gondii MYR1 is a recently identified dense granule protein that is required for the export/secretion of multiple dense granule effectors (including GRA24, GRA25 and GRA16;(15, 20, 21)) and was discovered based on its role in mediating T. gondii -specific activation of the transcription factor c-Myc(14). When we infected PHT cells with T. gondii lacking MYR1 (RH:Δ MYR1 ) and complemented control parasites (RH: Δ MYR1 : MYR1c ), we found that CCL22 production by PHT cells was entirely dependent upon MYR1 ( Figure 4F ), which provides strong evidence that T. gondii CCL22 induction in PHT cells is driven by (a) MYR1-dependent secreted effector(s).…”
Section: Resultsmentioning
confidence: 99%
“…Proteomic analysis of proteins that coimmunoprecipitated with GRA44 revealed interactions with known secreted proteins, including numerous GRAs. Among these interactors are GRA9, part of the intravacuolar tubular network (30); GRA16, an effector altering the host cell cycle through the p53 pathway (31); GRA25, a macrophagedependent immune modulator (32); and GRA33, GRA34, GRA45, GRA50, GRA52, and members of the multicopy mitochondrion association factor 1 (MAF1) family. MAF1 is involved in recruiting the host mitochondria to the PV membrane surface (33).…”
Section: Discussionmentioning
confidence: 99%